A single-dose comparison of four slow-release theophylline preparations in normal subjects. Issue 665 (March 1981) - Sharma, J. N.; Blackett, A.; Johnston, A.; Hathway, N. R.
Abstract : The plasma theophylline concentrations produced by 4 different slow release formulations, Theograd, Theodur, Theolair-SR and Rona-slophylline were measured over a 24-hr period in 8 healthy subjects. All 4 preparations maintained plasma levels over 12 hr and had similar AUC values when the difference in theophylline content was taken into account. Paired saliva and plasma theophylline concentrations gave a ratio of 1: 0·38, saliva: plasma, but with a large inter and intra individual variation.